IMPLEMENTASI DESAIN KOMUNIKASI VISUAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA MASA COVID-19 - Abdul Chalim; Vivin Devi Prahesti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This research was conducted in State Elementary School of Ngapanrejo in Bandongan District Magelang Regency with taking all students from grade 1 to 5 with overall 221 students as population. The research method was qualitative description systematically, factually, and accurately concerning the fact that happened in elementary schools. The aim research was that how to know the rate of student participation in accepting and understanding the lesson through visual communication, emphasizing they not to undertaking face-to-face learning. The resulting research was that the external obstacles affect teacher's explanation for students, influencing in understanding rates in the class and the obstacles were the signal, internet quota, and teaching method. The internal obstacles were gained from parents not caring toward students learning during the pandemic.